Gender Inequalities in Higher Education in Tanzania: Investigating the Influence of Parents ' Socioeconomic Status - Kavenuke, Patrick Severine; Kinyota, Mjege (Papers in Education and Development, 2024)
This study investigated the extent to which gender inequality manifests in higher education in Tanzania. Furthermore, through a gendered lens, the study investigated the influence of parents ' socioeconomic status on gender inequality among students who major in STEM and teacher education programmes. The study used a sample of 1714 students across four higher education institutions. It was found that gender is an aspect that forms inequality. For instance, the study revealed that gender differences were reflected in our sample, where female students were underrepresented in both STEM majors and teacher education majors. Also, parents ' education, occupation, educational background (in STEM), and income are some of the socioeconomic statuses that reinforce gender inequality. Finally, the implications for future research and policy are discussed. Keywords: femininity; gender inequality; higher education; masculinity; meritocracy